The regulation of agricultural land ownership in Hungary after land moratorium - Csák, Csilla (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
Arable land is one of the most valuable natural resources of the country, which shall comprise the nation’s common heritage; the responsibility to protect and preserve them for future generations lies with the State and every individual - we can read it in the Section (1) of Article P) of the Fundamental Law of Hungary. The new Act on the transaction of land (Act CXXII of 2013 on Transactions in Agricultural and Forestry Land), which was adopted by the Parliament on 21 June 2013, serves the realization of these purposes, and regulates the essential and dominant elements of land acquisition after the moratorium on land. The regulation formulates such legal institutions, substantive and procedural rules, which are able to guarantee the interest of the country. In the framework of the study we will present and analyze the EU’s expectations and principles, and on the other hand, the Hungarian solutions concerning to transaction of land.